On the contribution of nearly critical spin and charge collective modes to the Raman spectra of high-Tc cuprates - Caprara, Sergio; Enss, Tilman (Journal of magnetism and magnetic materials, 2009)
We discuss how Raman spectra are affected by nearly critical spin and charge collective modes, which are coupled to charge carriers near a stripe quantum critical point. We show that specific fingerprints of nearly critical collective modes can indeed be observed in Raman spectra and that the selectivity of Raman spectroscopy in momentum space may also be exploited to distinguish the spin and charge contribution. We apply our results to discuss the spectra of high-Tc superconducting cuprates finding that the collective modes should have masses with substantial temperature dependence in agreement with their nearly critical character. Moreover, spin modes should be more diffusive than charge modes indicating that in stripes the charge is nearly ordered, while spin modes are strongly overdamped and fluctuate with high frequency.